Answer:
1/19
Step-by-step explanation:
<em>Answer:</em>
n²+3
<em>Explanation:</em>
The differences between the terms are not the same, so this is not "linear". Knowing that the sequence may have started with a 1, you can try subtracting the first number with a number to get 1, and use that number to subtract the rest.
4 - 3 = 1
7 - 3 = 4
12 - 3 = 9
19 - 3 = 16
28 - 3 = 25
In this case, subtracting 3 to all the numbers gave us perfect squares! So this means the nth term has to do with squaring the number and adding three afterward! This can be checked.
√1 = 1
√4 = 2
√9 = 3
√16 = 4
√25 = 5
As we found the values of these terms by subtracting three first and then finding its square root, the nth term will be the opposite; squaring and then adding three! Again, this can be checked!
1² + 3 = 4
2² + 3 = 7
3² + 3 = 12
4² + 3 = 19
5² + 3 = 28
Hope this helps !! :D
Answer:
7-5x
Step-by-step explanation:
Answer:
Using a Graph of a Line Identify the x-axis. A coordinate graph has a y-axis and an x-axis. The x …
Using the Equation of the Line Determine that the equation of the line is in standard form. The …
Using the Quadratic Formula Determine that the equation of the line is a quadratic equation. A
Step-by-step explanation:
4(3x−1)=3+8x−11
Simplify
4(3x−1)=3+8x−11
(4)(3x)+(4)(−1)=3+8x+−11(Distribute)
12x+−4=3+8x+−11
12x−4=(8x)+(3+−11)(Combine Like Terms)
12x−4=8x+−8
12x−4=8x−8
Subtract 8x from both sides.
12x−4−8x=8x−8−8x
4x−4=−8
Add 4 to both sides.
4x−4+4=−8+4
4x=−4
Divide both sides by 4.
4x/4=−4/4
x=−1